Research on the Impact of Venture Capital Strategy on Enterprise Innovation Performance: Based on Evidence of Investment Timing and Rounds - Li, Xiwen; Zhao, Yunjia (Frontiers in Environmental Science, 2022)
What kind of venture capital strategy is more conducive to promoting enterprise innovation? We use companies listed on the Growth Enterprise Market (GEM) from 2009 to 2017 as samples, and poisson regression method to empirically test the impact of venture capital investment timing and rounds of venture capital on entrepreneurial innovation performance.The results show that: (1) Venture capital can significantly improve firms' innovation performance;However, compared with the early investment, the late investment can significantly improve the firm's innovation performance.With the increase of investment rounds, the innovation performance of enterprises is significantly improved. (2) Investment timing has a significant negative moderating effect on the relationship between investment rounds and firm innovation, that is, late-stage investment will significantly weaken the positive impact of investment rounds on firm innovation.